1992
DOI: 10.1111/j.1365-2389.1992.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil solution composition and pH in urine‐affected areas of pasture

Abstract: New Zealand S U M M A R YChanges in soil solution composition and concentrations of exchangeable cations and mineral N in undisturbed cores of pasture soil were investigated in two experiments following applications of sheep urine to the cores. The major cations applied in the urine were K+ and Na+, and the major anions were HCO; and C1-. Addition of urine increased concentrations of exchangeable K+, Na+ and NH and measured ionic strength of the soil solution throughout the surface 15cm of soil, demonstrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 20 publications
5
58
0
1
Order By: Relevance
“…This relationship has also been observed in other studies (e.g. Haynes and Williams, 1992). Organic matter in the soils (total C and N) also correlated with NH + 4 concentrations in the soils (See Table 2).…”
Section: Correlation Between Soil Properties and N 2 O Fluxsupporting
confidence: 71%
“…This relationship has also been observed in other studies (e.g. Haynes and Williams, 1992). Organic matter in the soils (total C and N) also correlated with NH + 4 concentrations in the soils (See Table 2).…”
Section: Correlation Between Soil Properties and N 2 O Fluxsupporting
confidence: 71%
“…However, this study also found that the pH may decrease or remain unaffected, depending on the chemical functional group, rate of addition, decomposition, and the initial soil pH. The increase in pH in the pasture soil was also previously attributed to animal excreta (Haynes &Williams, 1992;Shand & Coutts, 2006;Brunetto et al, 2012).…”
Section: Resultsmentioning
confidence: 74%
“…Scorching of the vegetation is known to occur, depending on deposition rate and urea concentration (42), and it is a result of osmotic stress, NH 3 toxicity, or a combination of both (18,31,42). Plants and microbes respond similarly to hyperosmotic conditions (11), and adverse effects on microbial populations can therefore also occur.…”
Section: Discussionmentioning
confidence: 99%
“…Excess N in the diet of cattle is mainly excreted as urea in the urine (23), and understanding the regulation of urea turnover in urine patches is therefore of particular interest. Urea typically disappears from the soil solution within 24 to 48 h and is replaced by high concentrations of NH 4 ϩ (18,36). The accompanying increase in osmotic pressure and free NH 3 concentrations can lead to N 2 O emissions and other microbial stress reactions (12,40).…”
mentioning
confidence: 99%